Sistem Pengendalian Internal Pemberian Kredit Pada Bank Mandiri Kantor Cabang Pembantu Mandiri Mitra Usaha Stabat Kwala Begumit - Purba, Hesty Agnes Tesalonika; Mariyam; Nasution, Nina Andriany (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The internal control system implemented at PT. Bank Mandiri (Persero) MMU Stabat Kwala Begumit has been implemented well in accordance with the COSO model, taking into account five components; control environment, risk assessment, control activities, information and communication and monitoring activities. Apart from that, PT. Bank Mandiri (Persero) MMU Stabat Kwala Begumit also provides credit services based on SPK and work culture, so that offers of financial assistance in the form of credit are right on target and do not harm the Bank. This is supported by the percentage of active debtor payments reaching 93%. This research aims to create a systematic, factual and accurate description, picture of the facts related to the case study investigated regarding the internal control system in granting credit at PT. Bank Mandiri (Persero) MMU Stabat Kwala Begumit. The results of this research were achieved using qualitative research methods with a case study approach.